1996
DOI: 10.1111/j.1348-0421.1996.tb01109.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the CD55 and CD59, Membrane Inhibitors of Complement on HIV‐1 Particles as a Function of Complement‐Mediated Virolysis

Abstract: Previous studies have demonstrated that the murine monoclonal antibody (MoAb) NM-01 activates the human complement classical pathway resulting in lysis of human immunodeficiency virus (HIV). The present study was performed to determine the availability of the V3-loop of gp120 relative to the complement regulatory proteins, CD55 (DAF) and CD59 (HRF20) molecules on HIV. The results demonstrate that CD55 and CD59 exist on HIV virions, along with gp120 molecules. These findings suggest that activation of human com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Three-dimensional reconstruction of transmission electron microscopy images or other ultrastructural approaches will be necessary to clarify this important issue. Other evidence for lipid rafts on HIV-1 virion particles comes from electron microscopy studies showing localization of GPI-anchored proteins CD55 (DAF) and CD59 to one pole of the virions (36). A caveat is that the processing of virions in these earlier studies may have induced capping or clustering of the molecules as can occur in cells.…”
Section: Discussionmentioning
confidence: 93%
“…Three-dimensional reconstruction of transmission electron microscopy images or other ultrastructural approaches will be necessary to clarify this important issue. Other evidence for lipid rafts on HIV-1 virion particles comes from electron microscopy studies showing localization of GPI-anchored proteins CD55 (DAF) and CD59 to one pole of the virions (36). A caveat is that the processing of virions in these earlier studies may have induced capping or clustering of the molecules as can occur in cells.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, the gp120 Env does not bind complement (168). Moreover, during budding, HIV incorporates glycosyl phosphatidylinositol (GPI)anchored CD55 and CD59 as well as transmembrane CD46, which are downregulatory molecules that inhibit complementmediated damage to the virus (169). HIV also captures serum complement factor H, which plays a central role in protecting cells from complement by downregulating complement binding and in turn increases virulence (170)(171)(172).…”
Section: Antibody-mediated Complement Activationmentioning
confidence: 99%
“…Proteomics, lipidomics, and biochemical studies have shown that the HIV-1 envelope is enriched in lipids and proteins that are also markers for lipid rafts (3,11,16,21,48,96,109,119), and envelope lipids appear ordered like those in rafts (90). Immunofluorescence microscopy studies have revealed that Gag colocalizes/copatches with lipid raft markers in cells (59,98,105) and cofractionates with lipid raft markers in detergent-resistant membranes (DRMs) (9,31,32,53,59,84,85,98,104,107) although qualitative differences between canonical DRMs and Gag-containing DRMs have been noted (31,59,84).…”
mentioning
confidence: 99%